ChemInform Abstract: Rapid Synthesis of Novel Flowerlike K0.46Mn2O4(H2O)1.4 Hierarchical Architectures and Their Catalytic Degradation of Formaldehyde in Aqueous Solution. Issue 21 (27th May 2014) - Ahmed, Khalid Abdelazez Mohamed; Huang, Kaixun
Abstract Nanostructured microflower‐like birnessite type Mn oxide hierarchical architectures are hydrothermally synthesized from KMnO4 and NaF as a reductant in H2SO4 at low temperature (autoclave, 120 °C, 150 min).